Pharmacogenomic Variants Affecting Statins Response in Sri Lanka (Precision Medicine Communications, 2023)
Pharmacogenomic variants can influence the efficacy and toxicity of statins, which are commonly prescribed medications for managing cholesterol levels and reducing the risk of cardiovascular events. Statins work by inhibiting HMG-CoA reductase, an enzyme involved in cholesterol synthesis. Ranasinghe and colleagues investigated the diversity of pharmacogenetic variants of statins among Sri Lankans.  They compared the minor allele frequencies (MAFs) of 426 Sri Lankans with other populations. They observed the following MAFs in common genes usually associated with statins response and toxicity.  The MAF of SLCO1B1*5 (rs4149056 [T>C]) was 18.19% (95% CI: 14.53-21.85),  MAFs of CYP2C9*2 (rs1799853 [C>T]) and CYP2C9*3 (rs1057910 [A>C]) were 2.58% (95% CI: 1.08-4.08) and 10.30% (95% CI: 7.75-13.61), respectively, MAFs of rs2231142 (G>T) (ABCG2), rs7412 (C>T) (APOE) and rs20455 (A>G) (KIF6) variants were 10.68% (95% CI: 7.76-13.60), 3.52% (95% CI: 1.77-5.27) and 50.7% (95% CI: 45.96-55.45), respectively. They found the frequency of two variants higher in the Sri Lankan population compared to the Western and other Asian populations (rs20455 (A>G), CYP2C9*3 (A>C) and SLCO1B1*5 (T>C)). They concluded that genetic polymorphisms affecting efficacy of statins (KIF6 [rs20455], CYP2C9*3) and increased risk of statin-induced myotoxicity (SLCO1B1*5 and CYP2C9*3) were prevalent in higher frequencies among Sri Lankans compared with Western populations. Pharmacogenomics. 2023 Oct;24(15):809-819.  doi: 10.2217/pgs-2023-0149.